ANALISIS KINERJA KEUANGAN PT. TELEKOMUNIKASI INDONESIA, Tbk & PT. XL AXIATA, Tbk - Yohanes Suharsana; Ag Dwi Winarno (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2014)
Financial performance is a management level gauges success in managing the financialresources of the company. Approaches using Economic Value Added (EVA) in this study werebased that this approach is very good for measuring performance (management) company becausethe company is able to describe the efficiency of a given period. While the approach using MarketValue Added (MVA) based on, that MVA was able to describe how much wealth can be created bythe company management to investors and companies.This study aimed to measure the financial performance. PT. Telkom and PT. XL in period2009 until 2011 using the approach of Economic Value Added (EVA) and Market Value Added(MVA). From the results obtained that EVA and MVA PT. Telkom is positive.In 2009 & 2011 PT. XL has a negative EVA, this means that the company management isnot successful to raise the economic value on the company over its operations. In 2010 PT. XL has apositive EVA, this means that the management company has succeeded in giving economic value tothe company over its operations. PT. XL has a positive value of MVA, MVA value in 2009. Thepositive MVA value means that the management has been able to increase shareholder wealth.